2021
DOI: 10.1016/j.neuron.2021.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus converts dynamic entorhinal inputs into stable spatial maps

Abstract: Highlights d MEC inputs to the DG, CA3, and CA1 show different spatial coding properties d MEC inputs remap even more strongly than hippocampal principal cells d Hippocampal principal cell activity is more reliable and stable than their MEC inputs d Hippocampal principal cells allow improved spatial and contextual readout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 101 publications
11
44
0
Order By: Relevance
“…One recent study used calcium imaging to examine the dynamics of DG granule cells during learning of a sensory-guided T-maze task, and found that place field stability correlated with behavioral performance (Shen et al, 2021). Alongside other DG imaging studies showing high cross-day similarity of spatial representations in well-trained animals (Hainmueller & Bartos, 2018; Cholvin et al, 2021), we can speculate about the mechanisms underlying the observed 7.8% reactivation in the Full-T group relative to Day 1. While the mice generalized learning well (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…One recent study used calcium imaging to examine the dynamics of DG granule cells during learning of a sensory-guided T-maze task, and found that place field stability correlated with behavioral performance (Shen et al, 2021). Alongside other DG imaging studies showing high cross-day similarity of spatial representations in well-trained animals (Hainmueller & Bartos, 2018; Cholvin et al, 2021), we can speculate about the mechanisms underlying the observed 7.8% reactivation in the Full-T group relative to Day 1. While the mice generalized learning well (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Alongside other DG imaging studies showing high cross-day similarity of spatial representations in well-trained animals (Hainmueller & Bartos, 2018;Cholvin et al, 2021),…”
Section: Composition Of Sub-ensembles For Pattern Separationmentioning
confidence: 81%
“…First, SST interneurons recieve strongly facilitiating excitatory synaptic input and have other membrane properties that allow these cells to be activated by a high-frequency burst from just one pre-synaptic neuron 69 , 70 . In hippocampus, gaining input from local principal neurons and losing ENTm input may help stabilize local network activity after TBI 71 . Second, muscarinic-mediated depolarization can produce prolonged spiking in SST interneurons 72 .…”
Section: Discussionmentioning
confidence: 99%
“…This navigation strategy is referred to as wayfinding (i.e., world-centered, allocentric navigation). The medial temporal lobe (MTL), especially the hippocampus, which is strongly interconnected with the entorhinal cortex (EC; Cholvin et al, 2021 ), is important for wayfinding (Maguire et al, 1998 ). The right hippocampus is more strongly associated with wayfinding than the left hippocampus (Maguire et al, 1998 ; Nedelska et al, 2012 ; Laczó et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%